Notalgia paresthetica: treatment review and algorithmic approach. (18th May 2020) - Ansari, Ahmed; Weinstein, David; Sami, Naveed
Abstract: Background: Notalgia paresthetica (NP) is a sensory neuropathy of the back characterized by a well demarcated, hyperpigmented macule or patch located medial or inferior to the scapulae. Symptoms include localized pruritus and pain, and the clinical course consists of remissions and relapses. It can be an underrecognized and difficult disease to treat since conventional treatments for pruritus in inflammatory dermatosis have variable efficacy. There are a variety of treatment modalities, but strong evidence to suggest the superiority of any one treatment is lacking. Objective: This review describes the treatments that have been used for NP in the literature and evaluates their level of evidence with respect to their efficacy. We also present a treatment algorithm based on our analysis. Materials and methods: MEDLINE search was performed using the terms 'notalgia, ' 'paresthetica, ' and 'treatment.' All resulting articles have been included in this review. Results: Treatment options include topical agents (capsaicin, tacrolimus, anesthetic cream, and amitriptyline/ketamine), systemic agents (gabapentin, oxcarbazepine, and amitriptyline), procedural modalities (botulinum toxin A and narrowband UVB), and physical therapy. Conclusions: Treatment should begin with topical agents or physical therapy, then systemic agents, and finally procedural modalities. We recommend combining treatment options with physical therapy for sustained treatment response.